Analysis Of Leadership, Innovation, And Work Culture On The Performance Of Micro Enterprises Food Stalls Typical Papuan Menu In Fakfak District - Naria M. Jafar; Sri Rahayu; Titis Istiqomah; Putri Rahma Dayanti (Jurnal Scientia, 2024)
The typical micro and small culinary industry in an area such as Papua can be an inspiration and starting point for developing empowerment and improving community welfare in a sustainable manner for the government and all interested communities as well as becoming an icon and attraction for tourist visits. This research aims to find out whether leadership, innovation and work culture influence the performance of micro-enterprise food stalls with a typical Papuan menu in Fakfak Regency. This research method uses descriptive analysis with a quantitative analysis approach . Data was obtained through a direct survey of respondents who had been determined deliberately. The data obtained is given a weight value based on assessment indicators obtained from the results of preliminary research. Test the validity and reliability of the data in a gradual and structured manner using a triangulation and role sharing approach. The research results are presented in the form of a spider web diagram which is equipped with illustrations of shift share gap values, root cause analysis diagrams with weighting, Pearson correlation analysis , and regression equation models obtained from the SPSS version 2.3 statistical tool.